Thoracic paravertebral blockade - Nierodziński, Wojciech; Przybytko, Julian; Misiołek, Hanna (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
A history of paravertebral block, anatomy and techniques of its performance, including both the traditional method, i.e. resistance decrease, and the new techniques like nerve stimulation and USG imaging were discussed in detail in this paper. Special attention was paid to various possibilities of PVB application, with cardio- and thoraco-surgery being especially included. The significance of local anaesthetics use was emphasized in paravertebral spaces administration and their dosage. A small number of complications and easiness of its performance should encourage to its broad use in thoracosurgery and in selected cardiosurgical procedures.